Intuitive and Modular Software Architecture for Functional Electrical Stimulation Rehabilitation - Ricarte, Guilherme; Pinheiro, Lucas; Bó, Antônio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
This paper presents a novel software architecture developed for rehabilitation based on Functional Electrical Stimulation (FES). Its main focus lies in enabling healthcare professionals and end-users to monitor and re-configure corresponding control systems through an intuitive graphical interface that presents performance data in time. Furthermore, the system, based on the Robot Operating System (ROS), is designed to allow incorporation of new hardware, which may enable its use in different rehabilitation scenarios. This paper also presents a proof-of-concept case study where this architecture was implemented and tested for a FES-cycling exercise.